The Impact of the Thirteenth and Fourteenth Pensions on the Financial Situation of Pensioners Receiving Minimum Benefits in Poland in 2017-2023: A Comparative Analysis Before and After the Introduction of these Benefits - Banach, Mateusz (Wpływ trzynastej i czternastej emerytury na sytuację materialną emerytów pobierających minimalne świadczenia w Polsce w latach 2017-2023: analiza porównawcza przed i po wprowadzeniu tych świadczeń, 2025)
The aim of this study was to assess the effect of introducing additional benefits – the so-called 13th and 14th pensions – on the financial situation of retirees receiving minimum pension benefits in Poland. The author examined changes in three key indicators for 2017-2023: the ratio of the minimum pension to the net minimum wage, the degree to which the social minimum is covered by the pensioner’s total benefits, and the real value of the minimum pension. Methodology: Data from Statistics Poland, the Social Insurance Institution and the Institute of Labour and Social Affairs on minimum pension amounts, minimum wage, statutory extra benefits and inflation were used. Paired t-tests were employed to compare the mean indicator values before (2017-2018) and after (2019-2023) the introduction of the extra benefits. Results: The results indicate that the introduction of the 13th and 14th pensions significantly improved the material security of minimum-benefit retirees, namely the average real value of their income increased, and the gap between income and the social minimum was almost completely eliminated. However, the relative position of these pensioners in terms of the minimum wage worsened, as the minimum wage grew faster than minimum pension benefits.Implications and recommendations: Given the anticipated changes to the social security system, additional research is needed to find appropriate retirement solutions. Originality/value: The article provides a synthesis of important empirical data allowing for the assessment of the effectiveness of the implemented solutions. It presents completely new results that expand the existing knowledge in the field of social policy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 4, s. 1-12
Keywords: minimum pension; 13th pension; 14th pension; social minimum; elderly poverty; minimalna emerytura; trzynasta emerytura; czternasta emerytura; minimum socjalne; ubóstwo seniorów